2010
DOI: 10.3928/01477447-20100526-05
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Femoral Cutaneous Nerve Impairment After Direct Anterior Approach for Total Hip Arthroplasty

Abstract: The anterior supine approach for total hip arthroplasty (THA) offers the advantage of operating through a true intravascular and intranervous plane, but it places the lateral femoral cutaneous nerve at risk. The purpose of this study was to identify the incidence of and impairment relating to injury of the lateral femoral cutaneous nerve. We performed a retrospective chart review of 81 hips undergoing anterior supine THA from November 2005 through May 2007 to determine operative time, estimated blood loss, flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 9 publications
3
81
0
Order By: Relevance
“…We found an incidence of subjective LCFN dysesthesia in approximately 20% and objective hypoesthesia in approximately 60% of the patients. These values compare favorably with those reported previously [1,6], and according to Bhargava et al [1], symptoms in many of these patients improve with time. We believe that LCFN problems mainly are related to a reversible neurapraxia of the LCFN as a result of traction caused by the retractors rather than to an irreversible dissection injury.…”
Section: Discussionsupporting
confidence: 79%
“…We found an incidence of subjective LCFN dysesthesia in approximately 20% and objective hypoesthesia in approximately 60% of the patients. These values compare favorably with those reported previously [1,6], and according to Bhargava et al [1], symptoms in many of these patients improve with time. We believe that LCFN problems mainly are related to a reversible neurapraxia of the LCFN as a result of traction caused by the retractors rather than to an irreversible dissection injury.…”
Section: Discussionsupporting
confidence: 79%
“…This variation may be explained by different interpretations or lack of recognition of LFCN injury, or the diversity of skin incisions chosen for the anterior approach 2,16,33,34,38 . While some authors observed that most symptoms of LFCN paresthesia resolved after 6 to 24 months 12 , others reported only a small number of patients with complete resolution 13 . The present study showed that 2 parameters influence the potential risk of LFCN injury: the individual distribution pattern of the LFCN in the proximal aspect of the thigh, and the technique and skin incision used for the anterior approach.…”
Section: Course O F T H E Lat E R a L Femoral Cutaneous N E Rv E W I mentioning
confidence: 99%
“…The anterior approach to the hip joint takes advantage of the internervous plane between the sartorius muscle (femoral nerve) and the tensor fasciae latae muscle (superior gluteal nerve). Despite the soft tissue-preserving nature of the anterior approach, there is a great danger of damaging the lateral femoral cutaneous nerve (LFCN) [12][13][14] ; the literature shows diverse rates of injury to the LFCN of between 0.1% and 81% 13,[15][16][17] . Although injury to the LFCN does not represent a major neurological complication, patients may report numbness or a burning sensation in the anterolateral region of the thigh and, in the worst cases, dysesthesia.…”
mentioning
confidence: 99%
“…[8] A study of Barghava et al in 81 hips undergoing THA through DAA found that paresthesia was observed in only 12 cases (14.8%), of which 4 were resolved within 6 months, 6 were resolved by 1 year and 2 cases remained unresolved. [9] According to this study, frank numbness in the affected limb was not observed. [9] Kennon et al reported incidence of LFCN injury in only 5 out of 2,132 cases (<0.01%) with a curved transverse incision or short straight incision.…”
Section: Discussionmentioning
confidence: 99%
“…[9] According to this study, frank numbness in the affected limb was not observed. [9] Kennon et al reported incidence of LFCN injury in only 5 out of 2,132 cases (<0.01%) with a curved transverse incision or short straight incision. [10] One multicenter observational study found neurological impairment in 13 out of 1,152 patients who underwent THA through DAA: seven cases of palsy of the LFCN, five cases of numbness in the lateral aspect of the thigh and one case of anterolateral thigh paresthesia.…”
Section: Discussionmentioning
confidence: 99%